2021
DOI: 10.1200/jco.2021.39.15_suppl.e21039
|View full text |Cite
|
Sign up to set email alerts
|

Does denosumab offer survival benefits? Our experience with denosumab in metastatic non-small cell lung cancer patients treated with immune-checkpoint inhibitors.

Abstract: e21039 Background: Lung cancer is the leading cause of cancer-related death in the United States. Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of non-small-cell lung cancer (NSCLC). Denosumab is a humanized monoclonal antibody to RANK ligand used to prevent skeletal-related events of bone metastases in solid tumors. In preclinical and some clinical studies, denosumab have shown to have some anti-tumor properties. We are reporting the clinical outcomes in our NSCLC patients who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Another retrospective observational study evaluated the efficacy of anti-RANKL agents and ICIs in patients with stage IV NSCLC and skeletal metastases. This study, including 69 patients who received denosumab within 30 days of ICI therapy, suggested that an overlap in the duration of ICI and denosumab treatment for > 3 months is associated with improved OS and PFS in patients undergoing concomitant therapy 75 . Additionally, a study presented at the 22nd World Lung Cancer Congress in 2021 explored the efficacy of bone-targeted agents (BTAs) combined with ICIs in patients with advanced NSCLC and bone metastases.…”
Section: The Receptor Activator Of Nuclear Factor-κb Ligand (Rankl) I...mentioning
confidence: 87%
“…Another retrospective observational study evaluated the efficacy of anti-RANKL agents and ICIs in patients with stage IV NSCLC and skeletal metastases. This study, including 69 patients who received denosumab within 30 days of ICI therapy, suggested that an overlap in the duration of ICI and denosumab treatment for > 3 months is associated with improved OS and PFS in patients undergoing concomitant therapy 75 . Additionally, a study presented at the 22nd World Lung Cancer Congress in 2021 explored the efficacy of bone-targeted agents (BTAs) combined with ICIs in patients with advanced NSCLC and bone metastases.…”
Section: The Receptor Activator Of Nuclear Factor-κb Ligand (Rankl) I...mentioning
confidence: 87%
“…This intricate dynamic creates an immunosuppressive environment, potentially leading to immunotherapy resistance within the bone. Prior retrospective studies investigating bone modifying agents such as bisphosphates or denosumab in addition to immunotherapy are yet to demonstrate any difference in survival outcomes for these patients [ 41 , 42 , 43 ]. A single-arm study of second-line nivolumab combined with denosumab demonstrated the efficacy of this combination [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypocalcemia can occur as a manifestation of tumor lysis syndrome as well, which has been described with the use of both ICI and CAR-T cell therapies. Additionally, the use of denosumab (humanized mAb to RANK ligand) in combination with ICIs can increase the likelihood of hypocalcemia (83).…”
Section: Hypocalcemiamentioning
confidence: 99%